Elèves, apprentissages et « numérique » : regard rétrospectif et perspectives - Georges-Louis Baron (Nantes Université, 2014)
From audio visual aids to digital online resources, in the last 50 years, a series of waves have broken upon the educational system and then recessed. Each one has had its own characteristics, its own aims. The main focus has been upon substituting devices to teachers, individualizing teaching, sparking collaboration between learners, educating a generation of citizens able to take into account the stakes of those new technologies. Something has however remained constant: in France, the discussion about what represented those new technological waves has turned about whether they were rather teaching objects or tools for teaching, these two orientations leading to different organizational consequences. The following text studies this tension first from a historical and then a prospective point of view. It first presents the evolution of the great theoretical visions produced by research on educational technology and then discusses the current tendencies regarding installing new curricula.